Dr. Jose A. Pacheco B. - Pacheco Romero, José (2015)
Peasant's son, born in Huacho on 1 December 1901. He had since childhood the sweet taste of medical practice, since his father was the "doctor" of the locals, attending their health problems with the help of a beautiful encyclopedia medical and attentive sense of observation. Came to Lima for his secondary education at the Colegio Guadalupe, then pursue a career in medicine at the National University of San Marcos, covering the costs of their studies with the income he paid his qualities as a pianist, His love and knowledge music became in shaping up to two orchestras that animated many family gatherings.